Penerapan Metode Pembelajaran Permainan Edukatif Terhadap Hasil Belajar IPA di SDN Sungai Miai 7 Banjarmasin - Nana Citrawati Lestari; Yulianti Hidayah; Fathul Zannah (Journal on Education, 2023)
The use of various learning methods is naturally carried out by teachers as educators. Learning science in elementary schools requires the use of interesting learning methods to have a positive impact on learning outcomes. One of the learning methods that can be used by teachers for science learning is the educational game method. Several studies using the game method in learning activities show satisfactory results. However, very few studies with the title application of educational games to elementary science learning are found on the Google Scholar search page. Therefore researchers are interested in conducting research with the title "Application of Educative Game Learning Methods on Science Learning Outcomes at SDN Sungai Miai 7 Banjarmasin". Based on the title, the purpose of this research is to find out whether the application of educative game learning methods can improve learning outcomes. As per the title, this research was conducted at SDN Sungai Miai 7 Banjarmasin. This research method is classroom action research (CAR). Data was collected through test and non-test techniques by filling out a questionnaire. Tests are used to collect data on learning outcomes. The data obtained was then analyzed in a quantitative descriptive manner. The results of learning science by applying the educational game method at SDN Sungai Miai 7 Banjarmasin have increased from each meeting based on the average value and percentage of classical completeness.